The identity of Aphodius nodifrons Randall, 1838 (Coleoptera: Scarabaeidae: Aphodiinae) from Maine, United States of America, with designation of the lectotype and handwriting examples - Krell, Frank-Thorsten; Angus, Robert (Zootaxa, 2014)
John Witt Randall's Coleoptera types have been assumed to be lost. In London and Harvard, we found two syntypes of Aphodius nodifrons Randall, 1838, coming from the collection of Thaddeus William Harris. We designated the lectotype and synonymised Randall's species with A. pedellus (De Geer, 1774).